The Management of Heavy Equipment Retribution on the Increasing of Original Local Government Revenue in Ministry of Public Works and Public Housing of Aceh Jaya Regency - Irmayasa; Ismail (Budapest International Research and Critics University, 2020)
The purpose of this research is to find out and analyze the management of heavy equipment levies to increase original local government revenue of Ministry of Public Works and Public Housing Aceh Jaya Regency. And also To find out and analyze the management of heavy equipment rental services in original local government revenue of Ministry of Public Works and Public Housing Aceh Jaya Regency. The conclusion of the research shows that the management of heavy equipment levies on the increase in original local government revenue of Ministry of Public Works and Public Housing Aceh Jaya Regency both related to the planning, regulation and supervision of heavy equipment has not been going well. While the financing aspect shows that the large operational budget needed for heavy equipment maintenance causes and puts a burden on the region, because the budget comes from the Aceh Jaya Regency APBk. Whereas the original local government revenue of Ministry of Public Works and Public Housing Aceh Jaya Regency deposit is always below the target set, the heavy equipment solid has a great potential for increasing original local government revenue of Ministry of Public Works and Public Housing Aceh Jaya Regency. Management of heavy equipment rental services related to service procedures, service commitments and time of rental. In connection with the procedure of renting services, it can run well because in the service procedure for renting heavy equipment rental activities, it must fill out the form provided and attach an identity in the form of a Identity Card and then ferment it. This is going well and in accordance with the rules that have been determined so that it can run well. Likewise with the commitment to leasing heavy equipment has been agreed between parties both personal leasing and rental for groups. Likewise with the time of rental daily and also monthly is not a problem, but many do rent on a monthly basis.